2018
DOI: 10.1088/1748-9326/aa9cb5
|View full text |Cite
|
Sign up to set email alerts
|

Impact, efficiency, inequality, and injustice of urban air pollution: variability by emission location

Abstract: Reducing exposure to air pollution is an important goal for many local and national governments. Disparities in air pollution exposure by race, ethnicity, and socioeconomic class are well documented; reducing these disparities is another important policy target. Meeting both goals requires tools to evaluate how emission reduction options affect average exposures and exposure disparities. Here, we consider the role of emission location in implementing control strategies, and investigate the effect of two practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 28 publications
(46 reference statements)
0
48
0
1
Order By: Relevance
“…Studies analyzing patterns in greenhouse gas (GHG) emissions pinpoint disproportionalities across nations, class groups, and households (Baer 2009, Kennedy et al 2014. Analyses of air pollution from vehicle emissions identify the disproportional contribution of high-emitting vehicles (Cadle et al 1997, Nguyen andMarshall 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Studies analyzing patterns in greenhouse gas (GHG) emissions pinpoint disproportionalities across nations, class groups, and households (Baer 2009, Kennedy et al 2014. Analyses of air pollution from vehicle emissions identify the disproportional contribution of high-emitting vehicles (Cadle et al 1997, Nguyen andMarshall 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In that case, policy-makers can consider spatially targeted emission-reduction policies (e.g. truck-rerouting, low-emission zones, industry re-allocation) in some locations to produce the strongest benefits to environmental justice (Nguyen and Marshall 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Even fewer studies have used Chemical Transport Models (CTMs). The literature review to date has found only three studies that used the Comprehensive Air Quality Model with Extensions (CAMx) (Marshall, Swor, & Nguyen, 2014;Nguyen & Marshall, 2018), and the Community Multiscale Air Quality (CMAQ) modelling system (Fann et al, 2011). These studies examined how changes in emissions will change environmental inequity, and two are discussed in more detail.…”
Section: Methodologies For Assessing Air Pollutionmentioning
confidence: 99%
“…Similarly, many studies use the human health risks calculated through the National-Scale Air Toxics Assessment model (Chakraborty, 2009;Chakraborty et al, 2014;Collins et al, 2015Collins et al, , 2011Grineski et al, 2014), which models certain individual air toxics using U.S. EPA's Community Multiscale Air Quality (CMAQ) model at a 12km grid resolution. Very few papers model concentrations directly using detailed Chemical Transport Models (CTMs); three exceptions are the use of the Comprehensive Air Quality Model with Extensions (CAMx) by Marshall, Swor, and Nguyen (2014) and Nguyen and Marshall (2018); as well as the use of the Community Multiscale Air Quality (CMAQ) modelling system by Fann et al (2011). The benefit of using a CTM is illustrated in these papers;…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation